2015
DOI: 10.17507/jltr.0606.29
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-cultural Analysis of the Use of Hedging Devices in Scientific Research Articles

Abstract: Abstract-Hedging is a significant aspect of academic writing and it is an important resource for L2 writers (Hyland, 1994). Hence, this study set out to compare the frequency of hedges employed in different sections of research papers written by non-native English speaking authors (NNESA) and native English speaking authors (NESA). To this end, 40 research articles written by the two groups of authors was analyzed based on the taxonomy of hedges proposed by Salagar-Meyer (1994). The results showed that general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…The study's findings showed a lower rate of hedges and boosters in RAs written by Czech linguists, which indicates that "the tendency towards symbiosis in the small Czech linguistics community is still significant and tends to affect their rhetorical choices even when they write English medium-texts." Other cross-cultural studies on hedges, such as those of Vázquez Orta and Giner (2008), Hu and Cao (2011), Jalilifar 2011, and Rezanejad et al (2015), also point out that the way in which writers use hedges tends to be affected by several factors "comprising the social and cultural background of the writer, the epistemological and literacy tradition he/she is associated with, and the genre and disciplinary conventions" (Dontcheva-Navratilova 2016). In a similar attempt, the cross-cultural and cross-generic study by Lorés-Sanz et al 2010on interpersonality in written academic discourse, with a focus on the Spanish and English research article corpus, showed that the frequency of the use of hedges was "especially higher in the English subcorpus when compared with the Spanish subcorpus".…”
Section: Hedges In Previous Cross-cultural Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The study's findings showed a lower rate of hedges and boosters in RAs written by Czech linguists, which indicates that "the tendency towards symbiosis in the small Czech linguistics community is still significant and tends to affect their rhetorical choices even when they write English medium-texts." Other cross-cultural studies on hedges, such as those of Vázquez Orta and Giner (2008), Hu and Cao (2011), Jalilifar 2011, and Rezanejad et al (2015), also point out that the way in which writers use hedges tends to be affected by several factors "comprising the social and cultural background of the writer, the epistemological and literacy tradition he/she is associated with, and the genre and disciplinary conventions" (Dontcheva-Navratilova 2016). In a similar attempt, the cross-cultural and cross-generic study by Lorés-Sanz et al 2010on interpersonality in written academic discourse, with a focus on the Spanish and English research article corpus, showed that the frequency of the use of hedges was "especially higher in the English subcorpus when compared with the Spanish subcorpus".…”
Section: Hedges In Previous Cross-cultural Studiesmentioning
confidence: 99%
“…A number of researchers have attempted to present and revise different taxonomies of hedges, such as Hyland (1998aHyland ( , 2000, Salager-Meyer (1994), Vande Kopple (2002), and Crompton (1997), among others. It is remarkable that the two taxonomies of Hyland (1998a) and Salager-Meyer (1994) are widely used in various studies of hedges (for example, Rezanejad et al (2015), Bonyadi et al (2012), Vázquez Orta and Giner (2008), Tran and Duong (2013)) due to their influence and sufficiency.…”
Section: Types and Functions Of Hedgesmentioning
confidence: 99%
See 3 more Smart Citations